Forest Soils Properties and Management - Osman, Khan Towhid (Springer International Publishing : Imprint: Springer, 2013)
Forest soil characteristics are not only unique but their interpretation also differs from cropland soils. Just as there are diverse forest types, there are many soil variants that need different management. Today, forest plantations are being intensively managed for profitable timber, pulpwood and energy production. Site selection, species selection, site productivity evaluation, silvicultural treatments, and soil amendments need crucial soil information.   This book provides a comprehensive overview of the physical, chemical and biological properties of forest soils and their implications on forest vegetation. Topics discussed include:   ·         major forest types of the world and their associated soils ·         forest biomass and nutrient dynamics ·         organic matter turnover and nutrient recycling ·         forest soil disturbance ·         forest soil and climate change ·         forest soil management and silvicultural treatments   The text leads the reader from the basics to a comprehensive understanding of forest soil science.  Study questions at the end of each chapter help to reinforce concepts.   While the text will be of particular interest to undergraduate students in grasping the fundamentals, it will also be of interest to graduate students and professionals in forestry, agroforestry and soil science, including those involved in nursery operations and plantation management.